Possible Cardiac Adverse Effects Induced by Therapeutic Doses of Ciprofloxacin in Juvenile Rats - Omar J.Al-faris; Nada N. Al-Shawi; Maha D. Kako (College of Pharmacy University of Baghdad, 2017)
Ciprofloxacin is widely used in treating adults infected with Gram-negative bacteria. It is contraindicated in children, growing adolescents and during pregnancy due to joint toxicity. Its toxicity concerning other organs needs to be clarified. Thus, this study was designed to study the possible cardiac damage induced by two selected doses of ciprofloxacin in juvenile rats.Eighteenth healthy juvenile rats (4 weeks old and their weight 30 Â± 2 gm) were utilized in this study and divided into three groups. Group-I control; group II and group III, respectively injected IP with 25 mg/kg and 50 mg/kg ciprofloxacin every 12 hours for one week. Serum enzymes activities alanine aminotransferase (ALT), aspartate aminotransferase  (AST), creatin kinase -muscle brain isoform (CK-MB), and lactate dehydrogenase (LDH) were assessed. Histological examination of heart tissues was also performed. The results of this study showed that, ALT, AST and CK-MB enzymes were significantly elevated only in group III compared to control. LDH enzyme was elevated in both group II and III. Concerning histological examination of the heart's gross sections, the results obtained from this work demonstrated the degeneration and necrosis in the hearts of group II and III juvenile rats compared to control animals. In conclusion, our results showed that the selected therapeutic doses of ciprofloxacin utilized in this study caused cardiac damage in juvenile rats. Key words: Fluoroquinolones, cardiac adverse effects, juvenile rat .